Layanan Perpustakaan Skill Online dalam Menghadapi Pandemi Covid-19 - Hasbi Hasbi; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Gunawan Gunawan; Marlina Marlina; A. Asgar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The existence of the Covid-19 pandemic at the beginning of 2020 had an impact on normal human activities, including library activities that have been carried out so far. Activities to stop library services manually to avoid direct contact with users as an action to prevent and transmit Covid-19. The purpose of this service is to find out the concept of digital services that can be done and provide an analysis of the application of information communication for several online services. The research method used is community service activities, namely counseling, implementation and innovation services that are carried out online. The online skill library is a modern library that already uses an automated system in its operations and has a collection of library materials mostly in digital format that is stored in a computerized architecture and can be accessed via mobile phones. The result of this service is the need for online library services through the application of the online skill library concept with four main discussions, namely photoshop, kinemaster, mechanics and culinary. Several online skill libraries on the front pages of Facebook and Instagram provide information related to the latest information from tips on becoming a culinary entrepreneur from scratch, health literacy services in preventing transmission, and a database of research results related to Covid-19.